2011
DOI: 10.1055/s-0030-1250576
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric Analysis of Lung Transplantation Research Articles

Abstract: The number of publications and the scientific interest in lung transplantation has increased rapidly in recent years. Citations of articles published in the field of lung transplantation are increasing and the numbers of uncited articles are fewer compared to the average citations of articles and uncited articles in the field of medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…This indicates a growing trend of publishing highly influential articles in specialty journals compared with other higher impact factor journals. Other bibliometric analyses also tend to support this notion [Brandt et al 2010; Eshraghi et al 2011; Hennessey et al 2009; Loomes and van Zanten, 2013].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…This indicates a growing trend of publishing highly influential articles in specialty journals compared with other higher impact factor journals. Other bibliometric analyses also tend to support this notion [Brandt et al 2010; Eshraghi et al 2011; Hennessey et al 2009; Loomes and van Zanten, 2013].…”
Section: Discussionmentioning
confidence: 81%
“…A total of 12 of the highly cited articles in our investigation were guideline papers, which were all published in diabetes specialty journals. Several analyses have reported that highly influential reports/guidelines are often published in the specialty journals [Brandt et al 2010; Eshraghi et al 2011; Hennessey et al 2009; Loomes and van Zanten, 2013].…”
Section: Discussionmentioning
confidence: 99%
“…Scientometric analyses are increasingly used for evaluation processes, carrier decisions and assignment of funds . Moreover, scientometric analyses are helpful for learning the history and current status of a study field.…”
Section: Introductionmentioning
confidence: 99%
“…Top-cited articles on hypertension and tuberculosis, for example, tend to be published in general journals, whereas those on lung transplantation are usually published in specialized journals. [ 14 , 18 , 39 ] These findings suggest the need to develop measures to assess the significance of specific research papers that are more accurate.…”
Section: Discussionmentioning
confidence: 99%